Inelastic Form Factors for the 90Zr Nucleus with Short-Range Correlations Effect - Abdalsada, Israa Khalil.; Al-Rahmani, Altaf A. (Iraqi Journal of Science, 2024)
Short-range effect on C2, C3, C4 and C5 form factors in the 90Zr atomic nucleus was scrutinized. The charge density of the 90Zr was as well as scrutinized via the 1- and 2-body parts of cluster expansion in collaboration with harmonic functions of single particle. To incorporate the short-range effect in the 2-body part of cluster expansion, the Jastrow formula was used. Here, the core-polarization and model space participations are what lead to the form factors in 90Zr. The transition density of core polarization was calculated using the Tassie form, relying on the charge density. The elements of one body density matrix were determined by performing shell model computations using the computer code OXBASH together with the N50J interaction. The oscillator parameter and correlation parameter were applied to the existing calculations, where and are autonomously produced for each distinct nucleus by matching between the predicted and actual elastic form factors. A single value for each of and must be given for computing the density, elastic and inelastic form factors for diverse states in 90Zr. This work provides confirmation that the short-range effect substantially dominates existing computations, where taking this effect into account appears to be crucial to creating an important modification to the predicated findings which eventually leads to a noteworthy interpretation of the data across all assumed momentum transfers.